Comparison of the Flexural Performance and Behaviour of Fly-Ash-Based Geopolymer Concrete Beams Reinforced with CFRP and GFRP Bars - Hemn Qader Ahmed; Dilshad Kakasor Jaf; Sinan Abdulkhaleq Yaseen (Advances in Materials Science and Engineering)
A construction system with high sustainability, high durability, and appropriate strength can be supplied by geopolymer concrete (GPC) reinforced with glass fibre-reinforced polymer (GFRP) bars and carbon fibre-reinforced polymer (CFRP) bars. Few studies deal with a combination of GPC and FRP bars, especially CFRP bars. The present investigation presents the flexural capacity and behaviour of fly-ash-based GPC beam reinforced with two different types of FRP bars: six reinforced geopolymer concrete (RGPC) beams consisting of three specimens reinforced with GFRP bars and the rest with CFRP bars. The beams were tested under four-point bending with a clear span of 2000 mm. The test parameters included the longitudinal-reinforcement ratio and the longitudinal-reinforcement type, including GFRP and CFRP. Ultimate load, first crack load, load-deflection behaviour, load-strain curve, crack width, and the modes of failure were studied. The experimental results were compared with the equations recommended by ACI 440.1R-15 and CSA S806-12 for flexural strength and midspan deflection of the beams. The results show that the reinforcement ratio had a significant effect on the ultimate load capacity and failure mode. The ultimate load capacity of CFRP-RGPC beams was higher than that of GFRP-RGPC, more crack formations were observed in the CFRP-RGPC beams than in the GFRP-RGPC beams, and the crack width in the GFRP-RGPC beams was more extensive than that in the CFRP-RGPC beams. Beams with lower reinforcement ratios experienced a fewer number of crack and a higher value of crack width, while numerous cracks and less value of crack width were observed in beams with higher reinforcement ratio. Beams with the lower reinforcement ratios were more affected by the type of FRP bars, and the deflection in GFRP-RGPC beams was higher than that in CFRP-RGPC beams for the same corresponding load level. ACI 440.1R-15 and CSA S806-12 underestimated the flexural strength and midspan deflection of RGPC beams; however, CSA S806-12 predicted more accurately.